PENGARUH PENGGUNAAN APLIKASI QUIZIZZ DALAM PEMBELAJARAN DARING TERHADAP MINAT DAN HASIL BELAJAR SISWA DI SMP - Mustika Piliang, Fenny; Damanik, Risjunardi; Ayu Wiranda, Deva (Jurnal Metabio, 2022)
This study aims to examine the effect of using the Quizizz application in online learning on student interest and learning outcomes in junior high schools. This study is a quantitative study. The study population consisted of 66 students consisting of two classes. Sampling was carried out by total sampling, namely class VII-A and class VII-B. The number of students in each class was 33. The research instrument used was a test and questionnaire. Based on the results of hypothesis testing using the t-test, as obtained thitung 6.836 > ttabel (1.701) at a significance level of 0.000 < 0.05. Based on this, it can be concluded that the Sig. value < 0.05 and thitung value > ttabel, which means H_0 is rejected and 〖H〗_a is accepted. Thus, there is a significant influence between the scores in the experimental class and the scores in the control class. Based on the results of the hypothesis testing using the F-test, the calculated F-value is greater than the F-table (9.709 > 4.004) and the sig. value is less than 0.05 (0.003 < 0.05). Thus, Ha is accepted and H0 is rejected, indicating a significant effect of learning using the Quizizz application on student interest and learning outcomes. The study concluded that using the Quizizz application has an impact on the interest and learning outcomes of sevent